2013
DOI: 10.1021/bi301591e
|View full text |Cite
|
Sign up to set email alerts
|

Alternating Sites Reactivity Is a Common Feature of Thiamin Diphosphate-Dependent Enzymes As Evidenced by Isothermal Titration Calorimetry Studies of Substrate Binding

Abstract: Thiamin diphosphate (ThDP)-dependent enzymes play vital roles in cellular metabolism in all kingdoms of life. In previous kinetic and structural studies, a communication between the active centers in terms of a negative cooperativity had been suggested for some but not all ThDP enzymes, which typically operate as functional dimers. To further underline this hypothesis and to test its universality, we investigated the binding of substrate analogue methyl acetylphosphonate (MAP) to three different ThDP-dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…In the process we also provide evidence of the half-of-sites, or alternating sites, reactivity that is postulated to be a common feature of all ThDP-dependent enzymes (Schroder-Tittmann et al, 2013).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…In the process we also provide evidence of the half-of-sites, or alternating sites, reactivity that is postulated to be a common feature of all ThDP-dependent enzymes (Schroder-Tittmann et al, 2013).…”
Section: Introductionmentioning
confidence: 67%
“…Evidence for active-site coupling, giving rise to alternating site reactivity in ThDP-dependent enzymes, was first found in benzoylformate decarboxylase (Sergienko et al, 2000), and is now believed to occur in many such enzymes (Frank et al, 2007;Schroder-Tittmann et al, 2013). Nevertheless, crystal structures of ThDP-dependent enzymes often fail to show evidence of active-site asymmetry, perhaps due to crystal packing constraints or ligand saturation during crystallization.…”
Section: Active-site Couplingmentioning
confidence: 99%
“…The two TPP cofactors in the functional (ab) 2 heterotetramer are located at relatively close positions (16.5 Å for the nearest atoms), suggesting a possible structural influence between the two active sites. Kinetic and structural studies on various thiamine-dependent enzymes suggested a communication (alternating sites reactivity) between the cofactors in different protomers 31 32 33 .…”
Section: Resultsmentioning
confidence: 99%
“…thought that there is considerable communication between active sites in order to coordinate the ping-pong kinetics between active sites, such that catalysis alternates between active sites, giving rise to the 'half-of-the-sites reactivity' phenomenon that has been observed in transketolase 7 and other TPP-dependent enzymes [8][9][10][11] .…”
mentioning
confidence: 99%